TRANSDISIPLINARITAS DALAM PEDAGOGIK MODERN - Marwan, Edi (Jurnal Mentari, 2007)
Dalam perkembangan ilmu pengetahuan yang dipengaruhi oleh faktor-faktor sosiologi, politik dan ekonomi telah mengubah pandangan mengenai manusia dalam proses pendidikan. Pandangan pendidikan yang sempit yang dikenal sebagai pedagogisme berubah menjadi pendidikan sebagai suatu gejala sosial, ekonomi, politik dan bahkan pula meliputi gejala-gejala biologis dalam neuro science. Keseluruhan perkembangan ilmu pengetahuan tersebut juga mempengaruhi perkembangan ilmu pendidikan. Dan pendekatan pedagogik yang sempit diganti dengan pendekatan "transdisipliner" atau multidisipliner mengenai ilmu pendidikan. Kata kunci : Transdisiplinaritas, pedagogik In the development of science influenced by factors sociology, politics and economics has changed the outlook of the people in the educational process. Narrow a view of education which is known as pedagogisme turn to education as a symptom of social, economic, political and even also includes biological phenomena in neuro science. The overall development of science has also influenced the development of science education. And narrow pedagogical approach is replaced by a "transdisciplinary" or multidisciplinary about science education. Keywords: Transdisiplinaritas, pedagogic